2014
DOI: 10.1007/s00192-014-2359-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous posterior tibial nerve stimulation: evaluation of a therapeutic option in the management of anticholinergic refractory overactive bladder

Abstract: TPTNS is well tolerated and is effective in one half of the patients studied after they failed anticholinergic treatment. TPTNS could become a second therapeutic option before surgical treatment in the management strategy of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 18 publications
0
59
0
1
Order By: Relevance
“…The 13 papers reported 10 RCTs and 3 prospective cohort studies . Included studies were published between 2002 and January 2017 with 9 of the 10 trials and 2 of the 3 prospective observational studies published since 2009.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 papers reported 10 RCTs and 3 prospective cohort studies . Included studies were published between 2002 and January 2017 with 9 of the 10 trials and 2 of the 3 prospective observational studies published since 2009.…”
Section: Resultsmentioning
confidence: 99%
“…PTNS) in the treatment of patients with overactive bladder [8]. To our knowledge, this is the first trial to evaluate the effectiveness of T.C.…”
Section: Commentsmentioning
confidence: 96%
“…PTNS has proven to be an effective treatment option in managing refractory OAB patients [8]. Nevertheless, to our knowledge, there are no published trials comparing the effectiveness of T.C.…”
Section: Introductionmentioning
confidence: 97%
“…The NICE guidelines recommend PTNS as an option for patients who fail conservative therapy and for whom onabotulinumtoxinA injections or sacral neuromodulation is not an option. A study by Ammi et al [37] demonstrated an improvement in 53% of antimuscarinic refractory PTNS patients based on validated questionnaire results. Peters et al [38] described the long-term efficacy of PTNS in a randomized, double-blind trial of women with OAB undergoing PTNS for a total of 36 months.…”
Section: Posterior Tibial Nerve Stimulationmentioning
confidence: 98%